A multilateral agreement on investment: Convincing the sceptics - Zdenek Drabek (World Trade Organization (WTO), 1998)
Much has been recently written about the Multilateral Agreement on Investment (MAI) that has been negotiated by OECD countries. Perhaps even more has been said by the critics of those who would like to see an agreement of this kind extended among other countries. There has indeed been a great deal of toing and froing about the desirability of MAI and even misunderstandings about its merits. The principal question of this paper is whether there is any need for MAI. There are arguments in favour and against and this paper provides a short review. On balance, the positive aspects of a multilateral agreement should outweigh the negative ones. The novelty of the paper is the attempt to address the critical voices. Given the lukewarm reaction in some countries, it would seem sensible to pay more attention to these arguments - a feature that may only now become something of pressing need in the light of the difficulties encountered in the OECD negotiations.
Keywords: F02; F21; F33; 330; Multilateral agreement on investment; WTO; foreign direct investment; capital flows; development